(untitled) (Swiss Medical Weekly, 2021)
BACKGROUND Multidrug-resistant organisms (MDROs) are a public health threat. Single-centre interventions, however, are likely to fail in the long term, as patients are commonly transferred between institutions given the economic integration across borders. A transnational approach targeting larger regions is needed to plan overarching sets of interventions. Here, we aim to describe differences in diagnostic and infection prevention and control (IPC) measures in the fight against MDROs. METHODS In 2019, we systematically assessed diagnostic algorithms and IPC measures implemented for detection and control of MDROs at three tertiary academic care centres (Freiburg; Strasbourg; Basel). Data were collected using a standardised data collection sheet to be filled in by every centre. Uncertainties were clarified by direct contact via telephone or email with the data supplier. Internal validity was checked by at least two researchers independently filling in the survey. RESULTS All centres have established a primarily culture-based, rather than a nucleic acid amplification-based approach for detection of MDROs (i.e., vancomycin-resistant Enterococci [VRE], methicillin-resistant Staphylococcus aureus [MRSA], extended-spectrum beta-lactamase-producing Enterobacteriaceae [ESBL], carbapenemase-producing and carbapenem-resistant Gram-negatives [CPGN/CRGN]). IPC measures differed greatly across all centres. High-risk patients are screened for most MDROs on intensive care unit (ICU) admission in all centres; only the French centre is screening all patients admitted to the ICU for VRE, MRSA and ESBL. Patients colonised/infected by MRSA, quinolone-resistant ESBL Klebsiella spp. and CPGN/CRGN are isolated everywhere, whereas patients colonised/infected by VRE and ESBL are usually not isolated in the German centre. CONCLUSIONS In contrast to the French and Swiss centres, the German centre no longer uses isolation measures to control VRE and quinolone-susceptible ESBL. Overall, the French centre is more focused on intercepting MDRO transmission from outside, whereas the German and Swiss centres are more focused on intercepting endemic MDRO transmission. These findings point to important challenges regarding future attempts to standardise IPC measures across borders.